Latest Developments in International Standardization of Whole-Body and Hand-Arm Vibration - Martin LIEDTKE,; Jorg RISSLER; Uwe KAULBARS (Archives of Acoustics, 2013)
Latest developments in international standardization of whole-body and hand-arm vibration are pre- sented. In addition, two German projects are presented that might have impact on international work programs in the next years.